Control of phase transformations and microstructure for optimum realization of one-way and two-way shape memory effects in removable surgical clips. (15th December 2017) - Ryklina, E.; Korotitskiy, A.; Khmelevskaya, I.; Prokoshkin, S.; Polyakova, K.; Kolobova, A.; Soutorine, M.; Chernov, A.
Abstract: The functioning of a newly developed "smart" clip for permanent or temporary clipping of the blood vessels is based on one-way and two-way shape memory effects (SME and TWSME, respectively) of Ti-Ni alloy. The clip remains in the ready-to-close position before it is locally heated up to 40–45 °C. Once heated by a specially developed clip-holder device, it closes due to realization of the SME, thus softly clipping the vessel. Upon local cooling, the clip opens due to the TWSME realization and can be easily removed without trauma to the vessel. To solve the problem of realization of SME and TWSME in the required temperature ranges and with the best functional characteristics, a thermomechanical treatment of Ti-50.7 at.%Ni alloy for controlled precipitation of Ti3 Ni4 phase particles and subsequent martensitic transformations was developed. A special regime of the clip thermomechanical treatment, including hot rolling and post-deformation isothermal annealing (aging), SME training procedures, and special design of the clip, was developed to obtain the best combination of the recovery strain and recovery stress of the clip. The phase transformations and microstructure were studied using differential scanning calorimetry, X-ray diffractometry, and transmission electron microscopy. The functional properties of the clips were determined using a bending method for inducing strain. The bench tests of the clip confirmed the effectiveness of the optimized thermomechanical treatment and training regimes as well as the cross-shaped clip design. Graphical abstract: Highlights: The problem of realizing one-way and two-way shape memory effects for a proper functioning of a new removable surgical nitinol clip is solved. A special thermomechanical treatment including annealing-aging of Ti-50.7at.%Ni alloy provides the best combination of one-way and two-way recovery strains and their realization in the required temperature ranges. A special cross-shaped clip design allows realization of the recovery force sufficient for reliable clipping of blood vessels. Upon heating of thermomechanically treated alloy, continuous B19′→R → B2 transformation after the early aging stage or separate B19′→R and R → B2 transformations after the late aging stage are observed.